A Deeper Understanding on the Prohibition of Riba - Daryanani, Neelam (2008)
This paper focuses on understanding the reasons for the prohibition of interest. Lending without interest is a difficult concept to grasp for those educated in the Western system as interest is the backbone of all conventional modes of finance. This paper takes the several different perspectives to probe if there are valid reasons other than a religious prohibition on interest.